2018
DOI: 10.1101/373548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Chromosome-Scale Assembly of the En ormous (32 Gb) Axolotl Genome

Abstract: The axolotl (Ambystoma mexicanum) provides critical models for studying regeneration, evolution and development. However, its large genome (~32 gigabases) presents a formidable barrier to genetic analyses. Recent efforts have yielded genome assemblies consisting of thousands of unordered scaffolds that resolve gene structures, but do not yet permit large scale analyses of genome structure and function. We adapted an established mapping approach to leverage dense SNP typing information and for the first time as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…A proper understanding of the functional relationship between NTV, body build and fitness in aquatic/terrestrial environments in Triturus is still lacking (Gvo□dík and van Damme, 2006), and functional studies exploring this fitness landscape across intra and interspecific variation in NTV is an important next step in establishing a firm causal relationship between variation, performance and fitness. The recent availability of the first salamander genomes (Elewa et al, 2017; Nowoshilow et al, 2018; Smith et al, 2018) finally offers the prospect of sequencing the genome of each Triturus species and exploring the developmental basis for NTV and its functional consequences in the diversification of the genus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A proper understanding of the functional relationship between NTV, body build and fitness in aquatic/terrestrial environments in Triturus is still lacking (Gvo□dík and van Damme, 2006), and functional studies exploring this fitness landscape across intra and interspecific variation in NTV is an important next step in establishing a firm causal relationship between variation, performance and fitness. The recent availability of the first salamander genomes (Elewa et al, 2017; Nowoshilow et al, 2018; Smith et al, 2018) finally offers the prospect of sequencing the genome of each Triturus species and exploring the developmental basis for NTV and its functional consequences in the diversification of the genus.…”
Section: Discussionmentioning
confidence: 99%
“…Our goal is to obtain a genome-enabled phylogeny for Triturus and use it to reconstruct the eco-morphological evolution of NTV and aquatic/terrestrial ecology across the genus. As the large size of salamander genomes hampers whole-genome sequencing (but see Elewa et al, 2017; Nowoshilow et al, 2018; Smith et al, 2018), we employ a genome-reduction approach in which we capture and sequence a set of transcriptome-derived markers using target enrichment, an efficient technique that affords extremely high resolution at multiple taxonomic levels (Abdelkrim et al, 2018; Bi et al, 2012; Bragg et al, 2016; Gnirke et al, 2009; McCartney-Melstad et al, 2016; McCartney-Melstad et al, 2018). Using data concatenation (with RAxML), gene-tree summarization (with ASTRAL) and species-tree estimation (with SNAPP), we fully resolve the Triturus phylogeny and place the extreme body shape and ecological variation observed in this adaptive radiation into an evolutionary context.…”
Section: Introductionmentioning
confidence: 99%
“…We used these sequences as queries in Blast searches (tBLASTX) (Altschul et al, 1990) against publicly available axolotl genomic and transcriptomic databases and datasets. These included Sal-Site 2 (Smith et al, 2005;Baddar et al, 2015) and axolotl-omics 3 (Nowoshilow and Tanaka, 2020), in addition to transcriptome datasets from Bryant et al (2017) (GSE92429), (Dwaraka et al, 2018) (GSE116615 and GSE116777), (Nowoshilow et al, 2018) (PRJNA378970, PRJNA378982), and (Smith et al, 2019) (GCA_002915635.2), and (Schloissnig et al, 2021) (PRJNA520877, PRJNA644663, and PRJNA645452). Axolotl sequences that yielded significant alignments (query coverage > 90%, highest bit score) were subsequently used to run additional blast searches against the aforementioned axolotl transcriptomic/genomic databases using BLASTN (query coverage > 90%) to identify potential duplicates within axolotl.…”
Section: Identification Of Matrix Metalloproteases/tissue Inhibitors Of Mmps Sequences and Data Resourcesmentioning
confidence: 99%
“…5 ClustalW (Madeira et al, 2019) was used to align sequences and annotate protein domains using human MMPs as protein models. Source information identifiers for the MMPs discovered in this study, including established genome locations for axolotl MMPs (Nowoshilow et al, 2018;Smith et al, 2019), are shown in Supplementary Tables 1, 2. This same general approach was also used to extract 60 TIMP sequences from the axolotl and all the taxa above (Supplementary Table 3).…”
Section: Identification Of Matrix Metalloproteases/tissue Inhibitors Of Mmps Sequences and Data Resourcesmentioning
confidence: 99%
“…Finally, one of the most promised salamanders of this family to be used in regeneration studies is Pleurodeles waltl (Iberian Burns et al, 2017. d Bryant et al, 2017Caballero-Pérez et al, 2018;Tobias Gerber et al, 2018;Leigh et al, 2018;Nowoshilow et al, 2018;Rao et al, 2009;Smith et al, 2019;Stewart et al, 2013;Wu et al, 2013. e Eo et al, 2012.…”
Section: Introductionmentioning
confidence: 99%